PENGARUH PENYIMPANAN PADA SUHU RENDAH TERHADAP KANDUNGAN PROTEIN DAN SIFAT ORGANOLEPTIK TAHU - Amelda, Amelda; Ansharullah, Ansharullah; Faradilla, RH Fitri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2020)
ABSTRACTThe purpose of this research was to study the effect of suweg and sea lettuce flours formulation on the organoleptic assessment, physical characteristics, proximate values, and antioxidant activity of control and selected wet noodles. This study used a completely randomized design (CRD) using the formulations of suweg flour and sea lettuce flour (96:4), (94:6), (92:8), and (90:10). The data from the organoleptic assessment and the physical characteristics of the noodles were statistically analyzed using the Analysis of Variance (ANOVA). The results with significant effect then continued with the Duncan's Multiple Range Test (DMRT) at 95% confidence level (α = 0.05). Meanwhile, the analysis of the differences between selected and control noodles used the T-Test. The results show that the formulation of suweg flour and sea lettuce flour had a very significant effect on organoleptic color, aroma, texture, elasticity, and overall as well as water absorption, swelling power, cooking time, and cooking loss. The selected noodles based on the organoleptic and physical characteristics was the A1 formulation (96% suweg flour and 4% sea lettuce flour) with organoleptic assessment scores of color, aroma, texture, elasticity, and overall reached 3.63 (light brown), 2.83 (slightly aromatic sea lettuce), 3.50 (somewhat chewy), 3.66 (not easily broken), and 3.43 (slightly like), respectively. Meanwhile, the assessment of physical characteristics shows that the product had 99.25% water absorption, 13.81% swelling power, 90.00 seconds cooking time, and 41.60% cooking loss. The proximate values of selected noodles include 39.47% (wb) of water content, 2.89% (db) ash, 9.90% (db) protein, and 23.66% (db) crude fiber. Selected noodles with a concentration of 500 ppm have a free radical barrier percentage of 61.95%. The results show that the wet noodle products were less accepted (preferred) by the panelists but they met the standards, except for the moisture content.Keywords: wet noodles, suweg flour, sea lettuce flour.ABSTRAKTujuan penelitian ini adalah untuk mempelajari pengaruh formulasi tepung suweg dan tepung selada laut terhadap karakteristik organoleptik dan fisik mie basah serta nilai proksimat dan aktivitas antioksidan mie kontrol dan terpilih. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan menggunakan formulasi tepung suweg dan tepung selada laut (96:4), (94:6), (92:8), (90:10). Data hasil penilaian organoleptik dan karakteristik fisik mie dianalisis secara statistik menggunakan Analysis of Varians (ANOVA). Penilaian organoleptik dan sifat fisik mie yang berpengaruh dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf kepercayaan 95% (α=0,05). Sedangkan untuk analisis perbedaan mie terpilih dan kontrol menggunakan uji t (T-Test). Hasil penelitian menunjukkan bahwa formulasi tepung suweg dan tepung selada laut berpengaruh sangat nyata terhadap organoleptik warna, aroma, tekstur, elastisitas, keseluruhan, serta daya serap air, daya pengembangan, waktu pemasakan dan cooking loss. Mie terpilih berdasarkan karakteristik organoleptik dan fisik terdapat pada formulasi A1 (96% tepung suweg dan 4% tepung selada laut) dengan skor penilaian organoleptik warna 3,63 (coklat muda), aroma 2,83 (agak beraroma selada laut), tekstur 3,50 (agak kenyal), elastisitas 3,66 (tidak mudah putus), keseluruhan 3,43 (agak suka) sedangkan penilaian karakteristik fisik daya serap air 99,25%, daya pengembangan 13,81%, waktu pemasakan 90,00 detik, cooking loss 41,60% dan nilai proksimat mie terpilih meliputi kadar air 39,47%bb, abu 2,89%bk, protein 9,90%bk, dan serat kasar 23,66%bk. Mie terpilih dengan konsentrasi 500 ppm memiliki persen hambatan radikal bebas sebesar 61,95%. Berdasarkan hasil penelitian produk mie basah kurang diterima (disukai) oleh panelis namun telah memenuhi standar SNI terkecuali kadar air.Kata kunci:mie basah, tepung suweg, tepung selada laut.